Nilai-Nilai Karakter dalam Lirik Lagu Jereh Bu Guru dari Daerah Serang Banten - Syamsul Rizal (Universitas Negeri Surabaya, 2021)
The song of jereh bu guru is one of the folk songs in the city of Serang, Banten province, using the lyriks in the Javanese of Serang (Jaseng) regional language. The lyrics of the song have differences in language and pronunciation with other song lyrics, so it is interesting to study in depth. The purpose of this study is to dissect and interpret the values ​​of the characters contained in the lyrics of the song jereh bu guru. This research uses a qualitative approach. Data collection techniques in this study are observation, interviews, and documentation. The results of this study indicate that the character values ​​in the lyrics of the song jereh bu guru consist of religious values, discipline. Curiosity, social care, and responsibility.